Young MSM changed temporal HIV-1 epidemic pattern in Heilongjiang Province, China - Li, Qing-Hai; Wang, Jia-Ye; Liu, Si-Yu; Zhang, Yun-Qi; Li, En-Long; Wang, Yi-Ru; Zhang, Shu-Lei; Zhao, Wen-Bo; Liu, Shu-Lin; Chen, Xiao-Hong; Wang, Fu-Xiang (Frontiers in Microbiology, 2022)
Background: Human immunodeficiency virus type 1 (HIV-1) epidemic in China is featured by geographical diversity of epidemic patterns. Understanding the characteristics of regional HIV-1 epidemic allows carrying out targeted prevention and controlling measures. This seven-year cross-sectional study was conducted in Heilongjiang, one province of Northeast China, where newly diagnosed infection is fast increasing yearly but temporal HIV-1 epidemic trend is largely unknown. Methods: Information of 1006 newly diagnosed HIV-1 infected participants were collected before antiretroviral therapy during 2010-2016 in Heilongjiang province. HIV-1 genotype was identified based on the viral gag and env gene sequences. Recent infection was determined by Limiting-Antigen Avidity assays. Comparison analyses on the median ages, CD4 counts, proportions of stratified age groups and CD4 count groups and rates of recent HIV-1 infection among different population and sampling times were performed to understand temporal HIV-1 epidemic features. Results: Homosexual contact among men who have sex with men (MSM) was the main transmission route and CRF01_AE was the most dominant HIV-1 genotype. During 2010-2016, the HIV-1 epidemic showed three new changes: the median age continued to decline, the cases with a CD4 count more than 500 cells/μl (CD4hi cases) disproportionally expanded, and the recent HIV-1 infection rate steadily increased. MSM cases determined the temporal trend of HIV-1 epidemic here. Increase of young MSM cases (aged < 30 years) made the main contribution to the younger age trend of MSM cases. These young MSM exhibited a higher median CD4 count, a higher proportion of CD4hi cases and a higher rate of recent HIV-1 infection than cases aged 30 years and more. MSM infected by CRF01_AE virus mostly affected HIV-1 epidemic patterns among MSM population. Conclusions: Young MSM have become a new hotspot and vulnerable group for HIV-1 transmission in Heilongjiang Province, Northeast China. The rapid increase in the number of young MSM cases, mainly those with CRF01_AE infection, changed temporal HIV-1 epidemic pattern here. Measures for prevention and control of HIV-1 infection among this population are urgently needed in the future.